2007
DOI: 10.1038/sj.cgt.7701026
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery system of cytotoxic agents to tumors by focused sonoporation

Abstract: Recently, ultrasound-targeting microbubble destruction has been employed in molecular gene therapy, and a new potent nonviral gene transfer method known as 'sonoporation' has been developed. We investigated the efficiency of sonoporation toward growth inhibition of human gingival squamous carcinoma cell line, Ca9-22, in vitro and in vivo. The cytotoxicity of bleomycin (BLM) was investigated using flow-cytometric analysis and Hoechst's staining in vitro assay systems. We found that the delivery of BLM by sonopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 39 publications
1
84
0
Order By: Relevance
“…In in vivo gene delivery experiments under similar ultrasonic intensity, frequency and duration, the temperature rise was found to be less than 2 1C. 39 Interestingly, we also found that Optison alone could enhance gene delivery in peritoneal tissues at levels lower than ultrasoundmicrobubble-mediated delivery. These findings are in accord with the observation by Lu et al 37 that microbubbles alone significantly increase the gene transfer in mouse skeletal muscle in vivo even in the absence of ultrasound, but contrast to the observation by Manome et al 36 that no expression of delivered gene Figure 2 Hematoxylin-eosin staining of parietal and visceral peritoneum in rats.…”
Section: Discussionmentioning
confidence: 52%
“…In in vivo gene delivery experiments under similar ultrasonic intensity, frequency and duration, the temperature rise was found to be less than 2 1C. 39 Interestingly, we also found that Optison alone could enhance gene delivery in peritoneal tissues at levels lower than ultrasoundmicrobubble-mediated delivery. These findings are in accord with the observation by Lu et al 37 that microbubbles alone significantly increase the gene transfer in mouse skeletal muscle in vivo even in the absence of ultrasound, but contrast to the observation by Manome et al 36 that no expression of delivered gene Figure 2 Hematoxylin-eosin staining of parietal and visceral peritoneum in rats.…”
Section: Discussionmentioning
confidence: 52%
“…Based on these findings, we mutated the primary receptor binding subunit (CdtA) of the toxin to eliminate intoxication of normal cells. Sonoporation has been used to deliver a plasmid containing the A. actinomycetemcomitans cdtB gene into Ca9-22, a human gingival squamous cell carcinoma cell line (Iwanaga et al, 2007). Transfected cells underwent apoptosis when treated in vitro and in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study Hauff has demonstrated that 50% reduction of pancreas adenocarcinoma tumour growth can be obtained after three intra-tumoural administrations of plasmid encoding p16 combined with US (color Doppler mode, MI ÂŒ 1.5) and microbubbles [43]. Recently, a significant effect has been reported on gingival squamous carcinoma cells implanted in nude mice [44]. A complete suppression of tumour growth was obtained in mice transfected with Optison Õ and plasmid encoding cytolethal bacterial toxin A using a transducer of 1 MHz with an output of 2W/cm 2 and 50% DC.…”
Section: In Vivo Sonoporation Assisted Gene Deliverymentioning
confidence: 97%